Caracterização de possibilidades e contradições na implementação de um currículo crítico no ensino de ciências da natureza pela Secretaria de Educação do Estado de São Paulo - Viegas, Flávia Hidalgo (2018)
This work is aresearch, which theme is the characterization of foundations and curricular practices proposals for the natural sciences curriculum implementation by the educacional state network of São Paulo, in order to analyze the limits and contradictions existing between the foundation of the curriculum and the practices adopted. Inconsistencies were observed between justification and orientation of the curriculum proposal, presented in the official curriculum of the State of São Paulo (CESP-2013) and the curriculum used, which limitates the performance in a non- critical curriculum that does not meet the reality of the student. A methodological qualitative research approach will be used. Data will be collected through: document analysis.